Gene Flow Across Genus Barriers – Conjugation of Dinoroseobacter shibae’s 191-kb Killer Plasmid into Phaeobacter inhibens and AHL-mediated Expression of Type IV Secretion Systems - Patzelt, Diana; Michael, Victoria; Päuker, Orsola; Ebert, Matthias; Tielen, Petra; Jahn, Dieter; Tomasch, Jürgen; Petersen, Jörn; Wagner-Döbler, Irene (Frontiers in Microbiology, 2016)
Rhodobacteraceae harbor a conspicuous wealth of extrachromosomal replicons (ECRs) and therefore the exchange of genetic material via horizontal transfer has been supposed to be a major evolutionary driving force. Many plasmids in the roseobacter group encode type IV secretion systems (T4SS) that generally mediate transfer of proteins and/or DNA into host cells, but no experimental evidence of either has yet been provided. Dinoroseobacter shibae contains five ECRs that are crucial for anaerobic growth, survival under starvation and the pathogenicity of this model organism. Here we tagged two syntenous but compatible RepABC-type plasmids of 191 kb and 126-kb size, each harboring a T4SS, with antibiotic resistance genes and demonstrated their conjugational transfer into a distantly related roseo-bacter species, namely Phaeobacter inhibens. Pulsed field gel electrophoresis showed transfer of those replicons into the recipient both individually but also together documenting the efficiency of conjugation. We then studied the influence of externally added quorum sensing (QS) signals on the expression of the T4SS located on the sister plasmids. A QS deficient D. shibae null mutant (ΔluxI1) lacking synthesis of N-acyl-homoserine lactones (AHLs) was cultivated with a wide spectrum of chemically diverse long-chain AHLs. All AHLs with lengths of the acid side-chain >14 reverted the ΔluxI1 phenotype to wild-type. Expression of the T4SS was induced above wild-type level. We hypothesize that conjugation in roseobacters is QS-controlled and that the QS system may detect a wide array of long-chain AHLs at the cell surface.